The Russian Brassicaceae collection – from N.I. Vavilov and E.N. Sinskaya till nowadays - A. M. Artemyeva; A. G. Dubovskaya; N. G. Kon’kova (Вавиловский журнал генетики и селекции)
This article  presents the  history  of the  formation  of the  Russian state  Brassicaceae  collection  maintained at  the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). Nowadays this one of the world’s richest collections encompasses more than 10,750 accessions of different status from 32 species and 11 genera: vegetable, fodder, oilseed, spicy, ornamental crops and continues to grow through collecting missions and exchange of material. The first intraspecific botanical  and agrobiological ecologo-geographical divisions of many crops – cole, turnip, radish, small radish, Swede – were performed by E.N. Sinskaya and T.V. Lizgunova over years of research. These unique works have been continued by M.A. Shebalina and L.V. Sazonova: the cultivar types of Chinese cabbage and pakchoi have been determined; the development of the classifications of white cabbage, broccoli, small radish, turnip is being  continued. The objective laws of variability of valuable biochemical  traits are presented; a comparative analysis of nutritive and biologically active substances, primarily secondary metabolites, allowed us to determine specific biochemical  compounds: those common for the related  species Brassica oleracea and B. rapa but occurring in them at different frequencies and those unique for species, subspecies and separate cultivar types; this is the beginning of taxonomic studies. With phytopathological studies, the common diseases of Brassicas in the northwestern part of Russia were determined, and the level of their distribution and development depending on the crop was shown. Genetic studies of the Brassicaceae collections at VIR include DNA analysis to search for duplicates in the collections, to compare original seeds  and the seeds  after reproduction and to assess the authenticity of saved accessions, to assess biodiversity, including that of new material from collecting missions, to develop phylogenetic studies. Chromosome loci controlling flowering time, morphological and biochemical  traits were determined by QTL analysis and association mapping, the molecular  markers found  are used for screening the collection and breeding material. The sources and donors of traits valuable for modern breeding directions have been found for use in various breeding programs.